Low noise figure C+L-band erbium-droped fiber amplifier - Hangdong ZHANG; Li ZHAN (Dianxin kexue)
A new configuration of the low noise figure C+L-band erbium-doped fiber amplifier was proposed and demonstrated.In the proposed configuration,a preamplifier was used to reduce the noise figure,and an improved double-pass configuration with a fiber bragg grating was employed to enhance the L-band gain and while to reduce the noise figure.The experiment results demonstrate that the noise figure in the new broad-band amplifier was improved by −2 dB,and the gain was enhanced up to above 25 dB over the region from 1 525～1 605 nm.